Localized electron heating during magnetic reconnection in MAST. (16th August 2016) - Yamada, T.; Tanabe, H.; Watanabe, T.G.; Hayashi, Y.; Imazawa, R.; Inomoto, M.; Ono, Y.; Gryaznevich, M.; Scannell, R.; Michael, C.
Abstract: Significant increase in the plasma temperature above 1 keV was measured during the kilogauss magnetic field reconnection of two merging toroidal plasmas under the high-guide field and collision-less conditions. The electron temperature was observed to peak significantly at the X -point inside the current sheet, indicating Joule heating caused by the toroidal electric field along the X -line. This peaked temperature increases significantly with the guide field, in agreement with the electron mean-free path calculation. The slow electron heating in the downstream suggests energy conversion from ions to electrons through ion-electron collisions in the bulk plasma as the second electron heating mechanism in the bulk plasma. The electron density profile clearly reveals the electron density pile-up / fast shock structures in the downstream of reconnection, suggesting energy conversion from ion flow energy to ion thermal energy as well as significant ion heating by reconnection outflow.